Strategies for optimal management of pediatric acute agitation in emergency settings - Mohsen Saidinejad; Ashley A. Foster; Genevieve Santillanes; Joyce Li; Dina Wallin; Isabel A. Barata; Madeline Joseph; Emily Rose; Tabitha Cheng; Muhammad Waseem; Kathleen Berg; Gwendolyn Hooley; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Acute agitation in youth is a challenging presentation to the emergency department. In many cases, however, youth can be behaviorally de‐escalated using a combination of environmental modification and verbal de‐escalation. In cases where additional strategies such as pharmacologic de‐escalation or physical restraint are needed, using the least restrictive means possible, including the youth in the decision‐making process, and providing options are important. This paper reviews specific considerations on the approach to a youth with acute agitation and strategies and techniques to successfully de‐escalate agitated youth who pose a danger to themselves and/or others.